Enumeration of bifidobacteria in animal intestina samples - V. Rada; J. Petr (Veterinární Medicína, 2002)
TPY agar supplemented with mupirocin (100 mg/liter) and glacial acetic acid (1 ml/liter) was effective in the enumeration of bifidobacteria in animal (11 species) fecal or intestinal samples. On the other hand, less than 50% of isolates from pig feces were identified as Bifidobacterium sp. using this medium. Subsequently TPY agar modified by the addition of mupirocin (100 mg/liter), glacial acetic acid (1 ml/liter), and colistin (25 mg/liter) was developed for the enumeration of bifidobacteria in pig feces. The results suggest that the bifidobacteria selective media should be chosen in respect of the animal species origin of the samples tested.